2015
DOI: 10.1074/jbc.m115.664490
|View full text |Cite
|
Sign up to set email alerts
|

Biological Relevance and Therapeutic Potential of the Hypusine Modification System

Abstract: Background: Hypusine modification of the eukaryotic initiation factor 5A (eIF-5A) represents a conserved post-translational modification that regulates translation. Results: Deletion of hypusine modification enzymes exerts strong phenotypes. eIF-5A2-deleted animals are viable and fertile. Conclusion: Both enzymatic steps of hypusine modification are essential for mammalian homeostasis, whereas the cancerrelated isoform eIF-5A2 is dispensable. Significance: eIF-5A2 might represent a safe therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 95 publications
7
51
0
Order By: Relevance
“…The generation of knockout mice of eIF5A1, Dhps or Dohh revealed that all three are essential for early embryogenesis, whereas heterozygous mice are viable and fertile (Nishimura et al 2012; Pallmann et al 2015; Sievert et al 2014; Templin et al 2011); thus, hypusination of eIF5A1 is essential for survival and development of mammals. Interestingly, homozygous eIF5A2 knockout mice are viable and fertile (Pallmann et al 2015).…”
Section: Roles Of Hypusination In Cell Growth and Tumor Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of knockout mice of eIF5A1, Dhps or Dohh revealed that all three are essential for early embryogenesis, whereas heterozygous mice are viable and fertile (Nishimura et al 2012; Pallmann et al 2015; Sievert et al 2014; Templin et al 2011); thus, hypusination of eIF5A1 is essential for survival and development of mammals. Interestingly, homozygous eIF5A2 knockout mice are viable and fertile (Pallmann et al 2015).…”
Section: Roles Of Hypusination In Cell Growth and Tumor Developmentmentioning
confidence: 99%
“…Interestingly, homozygous eIF5A2 knockout mice are viable and fertile (Pallmann et al 2015). Whether this is due to functional redundancy of eIF5A1 and eIF5A2 remains to be investigated.…”
Section: Roles Of Hypusination In Cell Growth and Tumor Developmentmentioning
confidence: 99%
“…We have recently observed that brusatol has a remarkable efficacy in protecting rat insulin-producing b cells against dysfunction and destruction induced by the proinflammatory cytokines IL-1b and IFN-g, and that this possibly occurred via inhibition of iNOS induction by a posttranscriptional mechanism (16). The biosynthesis of certain proteins is controlled by the translation factor eukaryotic initiation factor 5A (eIF5A) (17). The unique hypusine modification of eIF5A, in which an aminobutyl moiety is transferred from spermidine to a lysine residue, is a crucial requirement for eIF5A translation of the specific mRNAs, i.e., mainly mRNAs containing proline-rich Pro-Pro-Pro (PPP) or Pro-Pro-Gly (PPG) sequences (18)(19)(20).…”
mentioning
confidence: 99%
“…Proteins containing such proline repeats include proteins regulating key functions in growth and development including actin/cytoskeleton-associated functions, RNA splicing/turnover, DNA binding/transcription, and cell signaling (27,33). eIF5A is a relatively stable protein, but it can be acetylated either at Lys 47 (a residue essential for activity) by certain histone acetyltransferases or on the deoxyhypusine residue by SSAT (34), suggesting that its function may be regulated by acetylation/deacetylation.…”
Section: Hypusine and Eif5amentioning
confidence: 99%
“…Vertebrates have a second gene encoding eIF5A2, which is not widely expressed and is not essential but is present in several cancers where it is associated with aggressive growth and a poor prognosis (27,29). Prevention of hypusine formation in eIF5A2 inhibits tumor growth and reduces expression of the oncogenic tyrosine kinase PEAK1 (35).…”
Section: Hypusine and Eif5amentioning
confidence: 99%